POSITIVE EFFECTS OF THE REFORMS IMPLEMENTED IN UZBEKISTAN ON THE EDUCATION SYSTEM - Ergashbaev Shokhbozbek Oybek ugli (International Scientific and Current Research Conferences, 2023)
In this thesis, scientific information is given in order to analyze the interdependence of the work carried out in the educational sector and the pedagogic system as a result of the reforms implemented in Uzbekistan and their socio-historical aspects.